A Perspective Study of Koumiss Microbiome by Metagenomics Analysis Based on Single-Cell Amplification Technique - Yao, Guoqiang; Yu, Jie; Hou, Qiangchuan; Hui, Wenyan; Liu, Wenjun; Kwok, Lai-Yu; Menghe, Bilige; Sun, Tiansong; Zhang, Heping; Zhang, Wenyi (Frontiers in Microbiology, 2017)
Koumiss is a traditional fermented dairy product and a good source for isolating novel bacteria with biotechnology potential. In the present study, we applied the single-cell amplification technique in the metagenomics analysis of koumiss. This approach aimed at detecting the low-abundant bacteria in the koumiss. Briefly, each sample was first serially diluted until reaching the level of approximately 100 cells. Then, three diluted bacterial suspensions were randomly picked for further study. By analyzing 30 diluted koumiss suspensions, a total of 24 bacterial species were identified. In addition to the previously reported koumiss-associated species, such as Lactobacillus (L.) helveticus, Lactococcus lactis, L. buchneri, L. kefiranofaciens and Acetobacter pasteurianus, we successfully detected three low-abundant taxa in the samples, namely L. otakiensis, Streptococcus macedonicus, and Ruminococcus torques. The functional koumiss metagenomes carried putative genes that relate to lactose metabolism and synthesis of typical flavor compounds. Our study would encourage the use of modern metagenomics to discover novel species of bacteria that could be useful in food industries.